Thoracic but not abdominal phase contrast magnetic resonance-derived aortic pulse wave velocity is elevated in patients with abdominal aortic aneurysm. Issue 5 (May 2015) - Abbas, Abeera; Cecelja, Marina; Hussain, Tarique; Greil, Gerald; Modarai, Bijan; Waltham, Matthew; Chowienczyk, Philip J.; Smith, Alberto
<x xml:space="preserve">Abstract</x> Objectives: Increased stiffening of the aortic wall could contribute to the development of abdominal aortic aneurysm (AAA). We investigated regional aortic wall pulse wave velocity (PWV) in patients with AAA. Methods: Forty-six men diagnosed with a small AAA and 42 control men were recruited from the AAA surveillance and screening programmes at Guy's and St Thomas' Hospital. Phase-contrast cardiovascular MRI was performed to determine regional PWV along the thoracic (PWVTHOR) and abdominal aorta (PWVABD). PWV over the total aorta (PWVTOTAL) was calculated from the combined regions. Results: PWVTOTAL was significantly higher in patients with AAA compared to controls (10.0 ± 2.1 versus 8.4 ± 1.6 m/s, respectively; P < 0.0001). The difference in total aortic PWV between groups was explained by increased thoracic PWV in patients with AAA compared to controls (PWVTHOR 9.9 ± 2.8 versus 8.1 ± 2.5 m/s, respectively; P < 0.01). In contrast, there was no difference in PWV measured over the abdominal region in AAA patients compared with controls (PWVABD 10.7 ± 3.3 and 10.1 ± 3.3 m/s, in AAA and control groups, respectively; P = 0.40). In multiple regression analysis, including the whole cohort, abdominal aortic diameter remained significantly associated with PWVTOTAL and PWVTHOR (standardized regression coefficients 0.22 and 0.19, respectively; each P < 0.05 after adjustment for age and mean arterial pressure), but not with PWVABD. Conclusion: AAA patients have a greater PWV in the thoracic but not abdominal aorta compared to control individuals. Greater abdominal aortic diameter in patients with AAA is likely to offset effects of intrinsic stiffening of the abdominal aorta on PWV.